Analysis for Non-covalent Bonds in Protein Structures Using the DV-Xα Method - Kajiyama, Takeru; Aramaki, Kota; Kanazaki, Kohei; Matsushima, Ayami (Science and Technology Research Centre Universitas PGRI Semarang, 2026)
Halogen atoms are increasingly recognized for their ability to form non-covalent halogen bonds in protein–ligand complexesy. To systematically evaluate these interactions, we employed the DV-Xα method to calculate bond overlap populations (BOPs) in protein structures containing halogenated ligands. Using the Protein Data Bank, we identified thousands of entries with fluorine, chlorine, bromine, or iodine atoms. Structural coordinates were extracted around the chlorine atoms of the ligand and subjected to ab initio calculations under multiple truncation schemes. The findings highlight the utility of DV-Xα calculations in characterizing weak interactions and provide insights for future computational drug design employing halogen-containing compounds.